Short communication. The effect of oestrus at slaughter on carcass and meat quality of gilts intended for dry-cured ham production - Calvo, S.; Ripoll, G.; Rodriguez-Sanchez, J. A.; Latorre, M. A. (Spanish Journal of Agricultural Research, 2010)
On the day previous to slaughter, a total of 467 Duroc × (Landrace × Large White) gilts with approximately 130 kg body weight and 242 ± 3 days of age intended for Teruel ham production were observed to detect oestrus. The behavioural manifestations described in the literature were used for this. A total of 24 gilts were positively detected and individually identified (O gilts). From the same gilts observed, a total of 24 that clearly did not manifest oestrus were also individually identified (NO gilts). Therefore, a total of 48 gilts were used to study the effect of the presence of oestrus at slaughter on carcass and meat quality. No carcass characteristics were affected by oestrus at slaughter. However, all the carcasses (100%) from NO gilts were suitable for cured ham while 12.5% of carcasses from O gilts were not suitable because of the lack of the minimum backfat thickness required (16 mm) (p=0.09). The influence of oestrus at slaughter on meat characteristics was scarce. Under our experimental conditions, it can be concluded that avoiding the slaughter of gilts in oestrus might be recommendable when a minimum covering fat in carcass is needed to improve the quality of the end product. However, new trials would be needed to confirm this.